1983
DOI: 10.1038/clpt.1983.55
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between digoxin and calcium antagonists and antiarrhythmic drugs

Abstract: The influence of several calcium antagonists and antiarrhythmic drugs on digoxin kinetics and actions were investigated in 36 healthy men during digoxin steady state (0.375 mg/day). The subjects were randomly assigned to three subgroups and each group received placebo (control) and two of the following regimens (doses three times a day) in a randomized sequence for 2 wk each: verapamil (80 mg) and nifedipine (10 mg), verapamil (120 mg) and gallopamil (50 mg), or propafenone (150 mg) and quinidine (250 mg). Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(56 citation statements)
references
References 5 publications
4
51
1
Order By: Relevance
“…Clinical drug-drug interactions were reported in the literature between digoxin (a good P-gp substrate) and other drugs, such as quinidine [97][98][99], verapamil [100 -102], talinolol [103], clarithromycin [104], itraconazole [105], erythromycin [106], and propafenone [101,107,108].…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…Clinical drug-drug interactions were reported in the literature between digoxin (a good P-gp substrate) and other drugs, such as quinidine [97][98][99], verapamil [100 -102], talinolol [103], clarithromycin [104], itraconazole [105], erythromycin [106], and propafenone [101,107,108].…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…A reduction in renal and non-renal clearance of digoxin is considered to be the source of the calcium antagonist-digoxin interference [12,13]. The increased digoxin plasma levels caused by concurrent administration of a calcium channel blocker are pharmacodynamically relevant, meaning that there is evidence for an enhanced positive inotropic effect due to the elevated digoxin concentrations [1]. Furthermore the alterations in the pharmacokinetics of digoxin caused by calcium antagonists lead to an increased risk of digitalis intoxication especially in the elderly [14].…”
Section: Introductionmentioning
confidence: 99%
“…Various calcium antagonists increase the plasma concentrations of digoxin [1][2][3][4][5][6][7][8]. Dihydropyridine substances (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac arrhythmia sometimes occurs in patients who are taking digoxin, 1,2) and thus antiarrhythmic drugs were often co-administrated with digoxin. In fact, antiarrhythmic or antianginal drugs were also prescribed for 25% and 21% of patients taking digoxin, respectively, in our hospital.3) Digoxin is well known to have only a narrow therapeutic concentration range (trough: 0.5-2.0 ng/ml), and to be prone to drug-drug interaction.4) Clinical reports suggested that the serum concentration of digoxin was elevated by amiodarone, 5-7) quinidine, [8][9][10] verapamil 11,12) and nicardipine, 13) and the daily dose of digoxin is adjusted based on a sophisticated serial monitoring of serum digoxin concentration.Digoxin has been found to be mainly excreted by tubular secretion and glomerular filtration, 4,14) and tubular secretion has been demonstrated to be mediated via MDR1 by using LLC-GA5-COL150 cells, which were established by transfection of MDR1 cDNA into porcine kidney epithelial LLC-PK 1 cells. 15,16) Herein, the effects of amiodarone, its active metabolite monodesethyl-amiodarone (DEA) amd quinidine on the transport of [ 3 H]digoxin was examined using LLC-GA5-COL150 cells to elucidate whether MDR1 was responsible for the drug interaction between digoxin and amiodarone or quinidine found in clinical use.…”
mentioning
confidence: 99%
“…4) Clinical reports suggested that the serum concentration of digoxin was elevated by amiodarone, 5-7) quinidine, [8][9][10] verapamil 11,12) and nicardipine, 13) and the daily dose of digoxin is adjusted based on a sophisticated serial monitoring of serum digoxin concentration.…”
mentioning
confidence: 99%